Tindak Tutur Menyilaq pada Masyarakat Sasak di Desa Gereneng Kecamatan Sakra Timur - Mudarman, Mudarman; Kurniawan, Muh. Ardian (Universitas Hamzanwadi, 2019)
This research is a pragmatic study which aims to describe the form and strategy of the speech acts that are dazzling to the Sasak people in Gereneng Village, Sakra Timur District. Data collection uses interview techniques, observation, and is supported by a Test questionnaire Completing the Discourse. Data analysis uses the extralingual equivalent method. The results of the study show that the form of the speech act menyilaq using a one-sentence speech, two-sentence speech, three-sentence speech, and speech in more than three sentences. Meanwhile, the strategy of silence is done in the order of the opening greetings> apologies> introducing oneself> introducing the owner of the title> delivering the contents / message> hope> asking permission to leave> thank you> closing greetings. In responding to speech acts, the community manifests them in the form of receptive speech and speech rejecting. In the speech accepting the promising strategy, while in the speech refusing to use the strategy: thank you> apology> argumentation> message.Keywords: speech acts; menyilaq; Sasak language; pragmatics.